Efficacy of traditional Chinese medicine Cordyceps sinensis as an adjunctive treatment in patients with renal dysfunction: a systematic-review and meta-analysis - Wu, Fenfang; Xu, Chunhua; Si, Xinlei; He, Fei; Xu, Kang; Zhang, Yu; Lin, Shan (Frontiers in Medicine, 2025)
ObjectiveThe effectiveness of using Cordyceps sinensis as an adjuvant therapy for patients with renal dysfunction (RD), especially acute kidney injury (AKI), is still a topic of debate. In response to the current conflicting data, the present meta-analysis was conducted to assess the clinical effectiveness of C. sinensis in the treatment of RD and to provide evidence for clinical practice.MethodsSeveral databases, including PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure (CNKI) and Wanfang, were systematically searched updated to March 25, 2024. We used the combined ratio (OR) and diagnostic ratio (DOR) to assess the therapeutic effect of C. sinensis. In addition, risk of bias was assessed by Cochrane Risk of Bias Assessment Tool.ResultsThe present meta-analysis ultimately incorporated 15 studies comprising a total of 1,310 patients with RD. We pooled estimated the sensitivity, specificity as well as DOR from patient-based analyses with 0.89 (95% confidence interval [CI]: 0.84–0.93), 0.69 (95% CI: 0.59–0.77) and 18.0 (95% CI: 8.0–39.0), respectively. Moreover, we calculated the combined positive likelihood ratio (PLR) as well as negative likelihood ratio (NLR) to be 2.8 (95% CI: 2.1–3.9) and 0.16 (95% CI: 0.10–0.27), respectively. Additionally, area under the curve (AUC) of the summary receiver operating characteristic (SROC) was calculated as 0.88 (95% CI: 0.85–0.90) reflecting prognostic accuracy. Subsequently, subgroup analysis indicated that the clinical efficacy of C. sinensis in northern Chinese patients with RD was superior to that of southern. On the other hand, C. sinensis significantly reduced patients’ blood creatinine levels, shortened the oliguria period, and increased urine osmolality, indicating it can improve the function of glomeruli and renal tubules.ConclusionOur results indicate that C. sinensis can be considered a dependable clinical treatment for individuals with RD. It may improve the function of glomeruli and tubules, promote the recovery of tubular function, and thus enhance the clinical therapeutic effects.Systematic review registrationwww.crd.york.ac.uk/PROSPERO/#recordDetails, identifier CRD42024559042.